The Use of Communicative Method in Translating Illustrated Children’s Book Mini Num, the Tardigrade - Utami, Ria Dwitasari; Tiwiyanti, Leni (STKIP PGRI Tulungagung, 2025)
This study aimed to determine the translation problems found in translating the children's picture book 'Mini Num, the Tardigrade' and the application of the communicative method that could be used to solve these problems. The writer further discussed the translation procedures applied in this study. The research method used was qualitative because in this paper, the writer involved more data and analyzed it based on theory by experts. The study resulted show that the writer used seven translation procedures: naturalization, translation using common words, contextual conditioning, modulation, paraphrase, cultural equivalent, and transposition. The translation results were simple but communicative and attractive according to the needs of children. It proved that the communicative method is more appropriate for translating children's books than the semantic method. This was because of the importance of communicative language for target readers of children, which the resulting text adjusted to children's reading abilities and the language culture that children use daily.